Death or survival with major morbidity in VLBW infants born at Brazilian neonatal research network centers - Guinsburg, Ruth (2016)
Objective: To analyze unfavorable outcomes at hospital discharge of preterm infants born at Brazilian public university centers.Methods: Prospective cohort of 2646 inborn infants with gestational age 23-33 weeks and birth weight 400-1499g, without malformations, born at 20 centers in 2012-2013. Unfavorable outcome was defined as in-hospital death or survival at hospital discharge with 1 major morbidities: bronchopulmonary dysplasia (BPD) at 36 corrected weeks, intraventricular hemorrhage (IVH) grades 3-4, periventricular leukomalacia (PVL) or surgically treated retinopathy of prematurity (ROP).Results: Among 2646 infants, 1390 (53%) either died or survived with major morbidities: 793 (30%) died; 497 (19%) had BPD; 358 (13%) had IVH 3-4 or PVL; and 84 (3%) had ROP. Logistic regression adjusted by center showed association of unfavorable outcome with: antenatal steroids (OR 0.70; 95%CI 0.55-0.88), C-section (0.72; 0.58-0.90), gestational age <30 (4.00; 3.16-5.07), being male (1.44; 1.19-1.75), small for gestational age (2.19; 1.72-2.78), 5th-min Apgar <7 (3.89; 2.88-5.26), temperature at NICU admission <36.0 degrees C (1.42; 1.15-1.76), respiratory distress syndrome (3.87; 2.99-5.01), proven late sepsis (1.33; 1.05-1.69), necrotizing enterocolitis (3.10; 2.09-4.60) and patent ductus arteriosus (1.69; 1.37-2.09).Conclusions: More than half of the VLBW infants born at public university level 3 Brazilian hospitals either die or survive with major morbidities.